Dramaturgy Study: The Story of “Si Pandir” on The Effectiveness of Village Fund Management - Cahyono, Suham; Sudaryati, Erina; Sawarjuwono, Tjiptohadi (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2024)
Purpose: The aim of this study was to uncover the intricacies of village fund budget management by offering a comprehensive portrayal of the behaviors exhibited by the key actors involved in village budget management, both in front and behind the scenes. The aim of this study focuses on the workings of the X village fund budget, highlighting the role of third parties in optimizing the utilization of the X village fund budget. Method: A qualitative method with a dramaturgical study approach is used in this study to answer the proposed study proposition Results: The findings indicate that the dynamics observed in the management of the X village fund budget can lead to optimal resource allocation aligned with the village's development objectives and the well-being of its community. This is because the village fund administrators engage in strategic budgetary maneuvers to achieve the utmost efficiency in budget management. The positive impact stemming from the proactive involvement of the village apparatus, colloquially referred to as "Si Pandir," is the promotion of equitable development and the enhancement of village welfare. Through collaboration with relevant government entities, the village apparatus can facilitate the provision of advanced and fair amenities for the village, fostering cooperation that benefits the entire community. Implications: The results of this study can be used for future research to develop an optimal village fund management concept, not only from the perspective of the related village apparatus but also involving the active participation of the local community. Novelty: This research elaborates on village fund management with the Pandir legend as the most popular folklore in Java.